2003
DOI: 10.1016/j.chieco.2003.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Japanese direct investment in China

Abstract: This paper examines the recent trends, characteristics and determinants of Japanese direct investment in China. To study these issues, we first use qualitative and survey data to compare Japanese direct investment in China with similar investment in other Asian countries. We found that within Asia, China is the largest recipient of Japanese direct investment, with Hong Kong and Thailand coming in second and third. 76.5% of Japanese direct investment in China is in manufacturing. Such concentration in manufactu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 13 publications
0
39
0
1
Order By: Relevance
“…The implication that inward FDI in an industry will take place only if the South's technology frontier achieves a certain minimum threshold is consistent with the location choice of multinational firms documented by Kellenberg (2007), Fung et al (2004), Globerman and Shapiro (2003), Wei (2000), and Cheng and Kwan (2000). Proposition 1 also implies a positive correlation between the risk sensitivity level and the required threshold of the South's technology frontier in order for FDI to take place.…”
mentioning
confidence: 77%
“…The implication that inward FDI in an industry will take place only if the South's technology frontier achieves a certain minimum threshold is consistent with the location choice of multinational firms documented by Kellenberg (2007), Fung et al (2004), Globerman and Shapiro (2003), Wei (2000), and Cheng and Kwan (2000). Proposition 1 also implies a positive correlation between the risk sensitivity level and the required threshold of the South's technology frontier in order for FDI to take place.…”
mentioning
confidence: 77%
“…Recent studies of the distribution of aggregate FDI flows among Chinese provinces or regions include Coughlin and Segev (2000), Cheng and Kwan (2000), Parker (2002), Gao (2005), and Fung, Iizaka, and Siu (2003). In all these studies, the wage is found to be a statistically significant, negative determinant of the value of FDI flowing into a Chinese province or region.…”
Section: Control-function Corrections For Omitted Attributesmentioning
confidence: 99%
“…The authors ascribe the observed difference in behavior to clustering by U.S. owned firms in capital intensive sectors and to the export-processing focus of Hong Kong owned enterprises. Fung, Iizaka, and Siu (2003) compare Japanese and Hong Kong flows into Chinese regions and also find that Hong Kong investment is more sensitive to wage differences. Our results, based on project-level data and conditional logit analysis, do not support this characterization of differences in behavior.…”
mentioning
confidence: 99%
“…Better developed regions with a superior quality of infrastructure can also be more attractive to foreign firms relative to others by including in our regressions the proxy, the number of telephone mainlines per 1000 people. Parker (2002), Fung, Iizaka andSiu (2003) as well as Fung, Garcia-Herrero, Iizaka and Siu (2005) show that at least in some instances, FDI is attracted to a Chinese province with a better infrastructure. Standard errors in parentheses * significant at 10%; ** significant at 5%; *** significant at 1%…”
Section: Ando and Kimura 2003)mentioning
confidence: 99%